**u**=2x+1 d**u**=2dx pl**u**gging in 0 and 2 into the**u**eq**u**ation to find the new limits of integration**u**(0) = 1**u**(2) = 5 answer is .5 ∫[1,5]**u**^.5 d**u**so n**u**mber 31 Answers · Science & Mathematics · 05/04/2008

(du/dx)+

**u**+au^(5/4)+**u**^4 = 0 so (du/dx) = -(**u**+au^(5/4)+**u**^4) and thus -du/(**u**+au^(5/4)+**u**^4) = dx so we reach the... x(**u**) to get the desired functional form**u**(x) Unfortunately, I'm not certain if...2 Answers · Science & Mathematics · 19/05/2008

Let

**U**= A vector = <**U**x,**U**y,**U**z> Let... = A/|A| Let V = The vector projection of**U**on A is = (**U**•A)Â**U**•A = (...1 Answers · Science & Mathematics · 14/03/2014

∫ [x /(10 - √x)] dx = let (10 - √x) =

**u**→ √x = 10 -**u**→ sq**u**are both sides: x = (10 -**u**)² → dx = 2...3(10)**u**² -**u**³] /**u**} d**u**= distrib**u**te and break it into: - 2 ∫ (1000/**u**) d**u**+ 2 ∫ [(300**u**)/**u**] d**u**- 2 ∫ [(30**u**²)/**u**] d**u**+ 2 ∫ (**u**³/**u**) d**u**= p**u**ll...1 Answers · Science & Mathematics · 17/02/2009

By definition

**u**.v x w = |v x w| |**u**| cosθ where θ is the angle between**u**and v x w... where Θ is the angle between v and w. So**u**.v x w = |v||w| sinΘ |**u**| cosθ and this is eq**u**al to |**u**||v...2 Answers · Science & Mathematics · 03/10/2009

**U**-substitution in an algebra class is only representative of simplification. For instance, you can change a part of the equation that has 4xy^2 into**U**, and simplify the problem using**U**, and then plug the 4xy^2 into the equation...4 Answers · Science & Mathematics · 31/07/2006

I'll let P(

**u**) denote the projection of**u**along V and O(**u**) =**u**- P(**u**). ...let be the dot product. We want to show, for all w in V, that (O(**u**),w) = (**u**-P(**u**),w) = ((**u**-v),w) = 0. Well, how do we find v? v ...1 Answers · Science & Mathematics · 23/01/2009

∫

**u**d**u**/(16 +**u**^2) Let w = 16 +**u**^2 then dw = 2**u**d**u**so (1/2) dw =**u**d**u**We now have (1/2) ∫ dw/w = (1/2) ln w = (1/2) ln (16 +**u**^2) + C3 Answers · Science & Mathematics · 09/04/2011

∫(

**u**+ 2)^2 * (**u**+ 1)^(1/2) d**u**from -1 to 0 Let z =**u**+ 1 => dz = d**u**∫(z + 1)^2 * z^(1/2) dz from 0 to 1 (Note the ...3 Answers · Science & Mathematics · 04/12/2013

4u OVER

**u**^2 PLUS**u**OVER**u**-1 = 4u/**u**^2 +**u**/(**u**- 1) = 4/**u**+**u**/(**u**- 1) = [4(**u**- 1) + 4u]/[**u**(**u**- 1)] = (8u - 4)/[**u**(**u**- 1)] = [4(2u - 1)]/[**u**(**u**- 1)] C over C^2 + 9c +20 MINUS...1 Answers · Science & Mathematics · 25/10/2013